Direct measurement of Coulomb-laser coupling - Azoury, Doron; Krueger, Michael; Bruner, Barry D.; Smirnova, Olga; Dudovich, Nirit (Scientific Reports, 2021)
The Coulomb interaction between a photoelectron and its parent ion plays an important role in a large range of light-matter interactions. In this paper we obtain a direct insight into the Coulomb interaction and resolve, for the first time, the phase accumulated by the laser-driven electron as it interacts with the Coulomb potential. Applying extreme-ultraviolet interferometry enables us to resolve this phase with attosecond precision over a large energy range. Our findings identify a strong laser-Coulomb coupling, going beyond the standard recollision picture within the strong-field framework. Transformation of the results to the time domain reveals Coulomb-induced delays of the electrons along their trajectories, which vary by tens of attoseconds with the laser field intensity.
CRIS-Team Scopus Importer:2023-04-20